2021
DOI: 10.1007/s00408-021-00460-8
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hamartoma Associated With Lung Cancer (PHALC Study): Results of a Multicenter Study

Abstract: Purpose Pulmonary hamartoma is the most common benign tumor of the lung. We analyzed a 20-year historical series of patients with pulmonary hamartoma undergoing surgical resection, aiming to evaluate the characteristics, the outcomes, and the association between hamartoma and lung cancer. Methods It was a retrospective multicenter study including the data of all consecutive patients with pulmonary hamartoma undergoing surgical resection. The end-points wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…These data are supported by the results of a recent study, which demonstrated PHs and lung cancer association in 10.5% of cases [11]. Similar results were registered by another research team which revealed that 26% of patients had associated cancer, 12% of them being diagnosed with extrapulmonary malignancies (breast, gastric, and colon carcinoma) [10]. In our study group, a history of breast cancer was registered in one case, but the possibility of a secondary cancer was excluded.…”
Section:  Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These data are supported by the results of a recent study, which demonstrated PHs and lung cancer association in 10.5% of cases [11]. Similar results were registered by another research team which revealed that 26% of patients had associated cancer, 12% of them being diagnosed with extrapulmonary malignancies (breast, gastric, and colon carcinoma) [10]. In our study group, a history of breast cancer was registered in one case, but the possibility of a secondary cancer was excluded.…”
Section:  Discussionsupporting
confidence: 86%
“…The “hamartoma” term derives from “hamartia”, which means “erroneous” or “faulty”, in Greek [ 8 ]. From a historical perspective, Eugen Albrecht used, for the first time in 1904, the term “hamartoma”, to characterize a local cellular and tissular proliferation, typically found in the organ of origin [ 10 ]. Three decades later, Goldsworthy has defined PH as a local benign proliferation of hyaline cartilage and bone [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusing capacity of the lung for carbon monoxide(DLCO) is a pulmonary function test that measures the pulmonary performance for gas exchange from inhaled air into the blood stream, thus representing a marker of lung damage and mostly intended for diffuse alterations of alveolo-capillary barrier.Indeed, DLCO is reduced in patients with emphysema, interstitial lung disease and pulmonary brosis as well as in various other lung diseases [1].In addition, DLCO has been related to postoperative morbidity, mortality and overall survival(OS) in patients with non-small-cell lung cancer(NSCLC), with low DLCO values negatively affecting OS probably because of the occurrence of pulmonary complications [2][3][4][5][6][7][8][9][10][11][12].In 2011, the ATS/ERS/IASLC proposed a new classi cation of lung ADC [13], which was issued by the World Organization of Health(WHO) in 2015 [14].There were introduced and reclassi ed several different patterns of ADC with peculiar pathological features and related clinical behaviours, well demonstrated and validated by several authors [15][16][17][18] and consequently holding prognostic relevance [19][20][21][22].Among them, low DLCO values -re ecting a reduced pulmonary function-has been associated to histopathological indexes of tumour aggressiveness [23] and these observations suggested that lung damage may be associated with tumour carcinogenesis.We aimed to investigate the relationship between DLCO and lung ADC histopathological aggressiveness and to evaluate if more aggressive ADC develop in more severely damaged lung.…”
Section: Introductionmentioning
confidence: 99%
“…The diffusing capacity of the lung for carbon monoxide(DLCO) is a pulmonary function test that measures the pulmonary performance for gas exchange from inhaled air into the blood stream, thus representing a marker of lung damage and mostly intended for diffuse alterations of alveolo-capillary barrier.Indeed, DLCO is reduced in patients with emphysema, interstitial lung disease and pulmonary brosis as well as in various other lung diseases [1].In addition, DLCO has been related to postoperative morbidity, mortality and overall survival(OS) in patients with non-small-cell lung cancer(NSCLC), with low DLCO values negatively affecting OS probably because of the occurrence of pulmonary complications [2][3][4][5][6][7][8][9][10][11][12].In 2011, the ATS/ERS/IASLC proposed a new classi cation of lung ADC [13], which was issued by the World Organization of Health(WHO) in 2015 [14].There were introduced and reclassi ed several different patterns of ADC with peculiar pathological features and related clinical behaviours, well demonstrated and validated by several authors [15][16][17][18] and consequently holding prognostic relevance [19][20][21][22].Among them, low DLCO values -re ecting a reduced pulmonary function-has been associated to histopathological indexes of tumour aggressiveness [23] and these observations suggested that lung damage may be associated with tumour carcinogenesis.We aimed to investigate the relationship between DLCO and lung ADC histopathological aggressiveness and to evaluate if more aggressive ADC develop in more severely damaged lung.…”
Section: Introductionmentioning
confidence: 99%